(untitled) (Research, Society and Development, 2021)
Acupuncture is an integrative practice with a dynamic and integral approach to the health-disease process. It is a method that can be used separately or associated with other therapeutic possibilities. Because of this, there was an interest in knowing the main uses of acupuncture in Primary Health Care in Brazil through an integrative review of the literature in order to identify how acupuncture has been addressed in the most recent published scientific works. This research is characterized as an integrative review of the literature, in which articles published in the period from 2015 to 2020 were analyzed, selected taking into account the relevance and timeliness of their information. Based on the theme “The use of acupuncture in primary care in Brazil”, the literature published in Portuguese was sought as a priority for the study, due to the updated content present in articles on this theme. Acupuncture has often been shown to be superior or equivalent to drug treatment, with the advantage of having irrelevant side effects compared to its effectiveness, in addition to being able to be administered at low cost to any patient. This theme still needs more careful investigation and the dedication of more researchers in the study of acupuncture as an alternative for the SUS user. However, it must be noted that there is already strong evidence that this is a practical, effective method with great power to become another alternative for those who do not have access to the private health network.